Political Theory After Deleuze - Widder, Nathan, 1970- (Deleuze Encounters., 2012)
Recent political theory has shifted decidedly towards ontology, the science of being, and thus towards examining fundamental concepts of identity, difference, space, and time. This new focus has reinvigorated questions concerning the nature ofpower, meaning, truth and agency, inspiring novel approaches to individual andcollective subjectivity, the emergence of political events and the relationshipbetween desire and politics. In this new study, Nathan Widder shows how Deleuzes philosophy both inspires and pressesbeyond political theorys ontological turn. Linkinghis thought to current political the.